Do better-educated couples share domestic work more equitably in Japan? It depends on the day of the week - Hertog, E; Kan, M-Y; Shirakawa, K; Chiba, R (Department of Sociology, University of Calgary, 2021)
This paper investigates the gendered division of labor in different types of domestic work within married couples in contemporary Japan. We analyze routine housework such as cleaning and cooking, non-routine housework such as home repairs, and care work by using the 2016 Survey of Time Use and Leisure Activities (Japan’s national time diary survey). Our core analysis is done using ordinary least squares (OLS) regressions on total domestic work time, routine housework time, non-routine housework time, and care time. We find that women’s domestic work time dwarfs men’s, and there is some variation by day of the week and education. On weekdays domestic work is almost exclusively the domain of women. On weekends we find evidence of compensatory behaviors for both men and women. Men, especially those with university education, catch up on all types of unpaid work while women, especially those with tertiary education, catch up on unpaid work mostly by spending more time caring for children. Looking at the family balance in sharing domestic labor we find that men increase their time on unpaid work on weekends proportionately more than women do. Consequently, within couples, wives’ share of all types of unpaid work is around 10% smaller on weekends compared to weekdays. In couples where wives have tertiary education, there is an additional reduction by several percentage points in their weekend share of domestic work time compared to weekdays. Our findings suggest that Japanese men’s long work hours contribute to gender inequality in domestic work participation. We also find that university education is associated with more equal sharing of domestic workload, indicating that socialization may play a role in bringing about greater egalitarianism in the domestic sphere in the future.